The biogeography of Indo-West Pacific tropical amphipods with particular reference to Australia - Myers, A. A.; Lowry, J. K. (Zootaxa, 2009)
The extant distribution of amphipods in the tropical Indo-Pacific can be understood only by reference to the positions of shallow seas during the past two hundred million years. Amphipods attributable to extant families, even genera, were in existence in Mesozoic times. A number of amphipod families can be recognized as Gondwanan in origin, but Laurasian families, except in fresh waters, are more difficult to identify. The tropical amphipod fauna of Australia/New Guinea is thought to have evolved in situ until at least 15 Ma, when the continent reached proximity with Asia. Parsimony Analysis of Endemicity of Indo-Pacific amphipod families supports this hypothesis.